Role of management devices in enacting strategy – case study of Shared Service Centre. Issue 4 (7th November 2016) - Harritz, Daniel
Abstract : Purpose: This paper aims to illustrate the role of management devices in enacting strategy and strategic decisions, resulting in the development of a Shared Service Centre (SSC) in a Danish municipality. It shows how devices interact in defending, rejecting and reframing strategy, leading to the closure of the SSC to pave the way for new strategic ideas. Design/methodology/approach: It uses a longitudinal case-based approach, which draws on actor-network theory, particularly Callon's (1998) notions of framing and overflowing. These notions help describe strategic events and processes by highlighting the active role of non-human entities, such as management devices, in enacting and reformulating strategy. Findings: Different devices have become key actants in shaping and formulating the new strategy in the municipality and the strategic decision to construct an SSC. However, different devices mobilise different localities that protest, reject and participate in the closure of the SSC through a reframing strategy. Research limitations/implications: The study is subject to the general limitations of case-based research. Thus, the propositions should be further investigated to elaborate the performative role of management devices. Practical implications: The findings facilitate a deeper understanding of factors triggering strategic development in the public sector. Also, it identifies aspects leading to failures by investigating how different devices allow local actors to stay connected and affect the SSC's creation. Originality/value: This study is the first to use a performative method to highlight the temporary and local nature of enacting strategic decisions to construct an SSC in the public sector.